Bioresorbable Drug-Eluting Scaffolds: A New Treatment Paradigm for Atherosclerotic Plaque - Rizzo, Toni (MD Conference Express, 2012)
Fully bioresorbable scaffolds (BRS) offer a revolutionary treatment approach within the field of interventional cardiology. Since BRS devices provide temporary mechanical support to the vessel wall and then subsequently disappear, the technology has the potential to overcome many of the safety concerns associated with metallic drug-eluting stents, such as late stent thrombosis, prevention of late lumen vessel enlargement, and difficulties with surgical revascularization and imaging artifact with multislice computed tomography [Bourantas CV et al. Int J Cardiol 2012; Serruys PW et al. Lancet 2009]. This article discusses the advances in BRS over the last 5 to 6 years.